(untitled) (Terr@ Plural, 2023)
Assessing the vegetation cover of a municipality is essential for monitoring and controlling land use and occupation. Therefore, the study aims to evaluate the evolution of areas with vegetation cover in the municipality of Guarulhos between the years 1986 and 2022, using Landsat-8 and Landsat-5 images acquired in the years 1986, 1991, 2013 and 2022. As a methodology the Normalized Difference Vegetation Index (NVDI) was applied to calculate vegetation. It is concluded that the municipality of Guarulhos has been showing a reduction in its area of vegetation cover, mainly due to irregular occupation related to the construction of the Rodoanel Trecho Norte, precisely the areas with the highest concentrations of vegetation in the municipality.